JHEA, volume 20, n°1, 2022 - Full Issue - Journal System (Journal of Higher Education in Africa, 2022)
Contents Researching Gender Relations in Africa: Directions and Landmarks in Feminist Research Methodology Josephine Akihire................................... 1 Feminist Postproverbial as a Panacea for Decolonising African Feminist Scholarship Olayinka Adebimpe Oyeleye...................23 What Has Worked or Failed with Feminist Scholarship in Academic Spaces in Africa? The Case of the School of Women & Gender Studies, Makerere University Jackline Kirungi......................................45 Re-membering Wangari Maathai’s Feminist Scholarship in her Autobiography Unbowed: One Woman’s Story Stephen M. Mutie..............................65 Feminist Scholarship, Femocracy and the Glass Ceiling in Zimbabwean Politics Patience Chadambuka......................83 Genre, handicap et santé sexuelle et reproductive au Cameroun : implication des acteurs sociaux et rapports aux politiques publiques Estelle Kouokam Magne, Irène Flore Chiewouo Kuetche & Félicité Djoukouo.......................107